A Model of Ontology Supporting COTS Component Selection Process in Management Information System Domain - Konys, Agnieszka; Wątróbski, Jarosław (Model ontologii wspomagającej proces wyboru składników COTS w dziedzinie systemów informatycznych zarządzania, 2010)
The main aim of this article is a proposal of ontology as a solution to support COTS components selection and evaluation in Management Information System (MIS) domain. On the basis of Computer World Report, five ERP systems were selected including their specified characteristics. A proposal of a model of ontology has to provide systematic and repeatable solution for COTS components selection in MIS domain, including individual preferences of an enterprise. The conclusions finish this paper.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 147, s. 189-204
Keywords: ontology; COTS software; management information systems; COTS components selection